O Estado de Alagoas no contexto regional nordestino - Paulo Rogério de Freitas Silva; Silvana Quintella Cavalcanti Calheiros (Confins)
The theme we've chosen for developing refers to the ruling spatial order in the State of Alagoas, located in Northeastern region of Brazil, and promotes a journey through the five centuries of territorial formation of this space. In order to develop this process, we considered the suggestion of spatial order, and so we seeked to understand the human actions that intervene in the current spatial order in Alagoas. It's about characterizing a situation where objects tend to perform some specific functions in each area and their processes are largely subject to the regulatory role of institutions and companies. In this connection, we started from the discussion about urbanization as a process that has reached society and territory in this century, after a long period of selective urbanization, both social and territorial. Urbanization as a process, where the residence of workers, including farm workers, is increasingly urban and the demographic turmoil and outsourcing are notable facts. This research has the character of documentary and bibliographical investigation, being a qualitative research with regard to the agents and immediate purposes of the creation of urban centers, analyzing the determinant processes for this genesis. We anticipate that the urban genesis in Alagoas takes place in greater number initially in Zona da Mata and in the Coast, to the detriment of Sertão or Agreste, and it has an economy without production, with localities that hardly ever produce for the generation of wealth.